Development of a conceptual model of the hydrologic response of tropical Andean micro-catchments in Southern Ecuador - Crespo, Patricio; Feyen, J.; Buytaert, W.; Célleri, R.; Frede, Hans-Georg; Ramírez, M.; Breuer, Lutz; Justus Liebig University Giessen (My University, 2012)
This paper presents a lumped conceptual model designed for simulating the rainfallrunoff response of mountain micro-catchments with natural vegetation located in the south of Ecuador. The conceptual model is mimicking the soil hydrology and consists of a maximum of three linear reservoirs in series. A two and three reservoir model structure were tested, respectively A GLUE uncertainty analysis was applied to assess the model performance. Simulation results of the discharge confirmed the applicability of the soil-based conceptual model structure for the selected study areas, during model calibration and validation. The three reservoir model best predicted the runoff, nevertheless the two reservoir model well captures the rainfall-runoff process of the micro-catchments with páramo vegetation. Although differences in climate regime, vegetation, and soil of the selected catchments runoff is strongly controlled by the precipitation and soil type, and the horizons contributing to runoff are defined by their antecedent wetness. Results confirm that the discharge is mainly controlled by lateral subsurface flow through the organic horizons, while during dry conditions the C-horizon and the bedrock mainly contribute to discharge. Lateral transport through the densely rooted top horizon and the litter layer occurs during storm events, being under those conditions the major discharge component. Overland flow is a local phenomenon, negligible in comparison to the other flow components.
Keywords: rainfall-runoff response simulation; mountain micro-catchments; reservoir model structure; ddc:570